Bleeding Independently associated with Mortality after noncardiac Surgery (BIMS): an international prospective cohort study establishing diagnostic criteria and prognostic importance. (January 2021) - Roshanov, Pavel S.; Eikelboom, John W.; Sessler, Daniel I.; Kearon, Clive; Guyatt, Gordon H.; Crowther, Mark; Tandon, Vikas; Borges, Flavia Kessler; Lamy, Andre; Whitlock, Richard; Biccard, Bruce M.; Szczeklik, Wojciech; et al.
Abstract: Background: We aimed to establish diagnostic criteria for bleeding independently associated with mortality after noncardiac surgery (BIMS) defined as bleeding during or within 30 days after noncardiac surgery that is independently associated with mortality within 30 days of surgery, and to estimate the proportion of 30-day postoperative mortality potentially attributable to BIMS. Methods: This was a prospective cohort study of participants ≥45 yr old having inpatient noncardiac surgery at 12 academic hospitals in eight countries between 2007 and 2011. Cox proportional hazards models evaluated the adjusted relationship between candidate diagnostic criteria for BIMS and all-cause mortality within 30 days of surgery. Results: Of 16 079 participants, 2.0% (315) died and 36.1% (5810) met predefined screening criteria for bleeding. Based on independent association with 30-day mortality, BIMS was identified as bleeding leading to a postoperative haemoglobin <70 g L −1, transfusion of ≥1 unit of red blood cells, or that was judged to be the cause of death. Bleeding independently associated with mortality after noncardiac surgery occurred in 17.3% of patients (2782). Death occurred in 5.8% of patients with BIMS (161/2782), 1.3% (39/3028) who met bleeding screening criteria but not BIMS criteria, and 1.1% (115/10 269) without bleeding. BIMS was associated with mortality (adjusted hazard ratio: 1.87; 95% confidence interval: 1.42–2.47). We estimated the proportion of 30-day postoperative deaths potentially attributable to BIMS to be 20.1–31.9%. Conclusions: Bleeding independently associated with mortality after noncardiac surgery (BIMS), defined as bleeding that leads to a postoperative haemoglobin <70 g L −1, blood transfusion, or that is judged to be the cause of death, is common and may account for a quarter of deaths after noncardiac surgery. Clinical trial registration: NCT00512109.